EMULGEL EKSTRAK ETANOL DAUN SUMAMBU (HYPTIS CAPITATA JACQ.) SEBAGAI KANDIDAT ANTIBAKTERI TERHADAP STAPHYLOCOCCUS AUREUS ATCC 25923 - Arviani; Nurul Izza Fersilia; M. Fariez Kurniawan; Rahma Artemisia (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
Hyptis capitata (sumambu) leaves are a traditional medicinal plant from the Lamiaceae family, commonly used to treat inflammation, swelling, pain, digestive disorders, fever, and wounds. The plant contains bioactive compounds such as oleanolic acid, alkaloids, terpenoids, and flavonoids, which may have antibacterial properties. To improve topical use, the leaf extract was formulated into an emulgel. This study aimed to evaluate the antibacterial activity of the emulgel containing ethanolic extract of H. capitata leaves against Staphylococcus aureus. The experimental study employed H. capitata leaves extracted by maceration using 96% ethanol. Phytochemical screening was conducted to identify active compounds, while the physical characteristics of the emulgel were assessed through organoleptic evaluation, spreadability, adhesiveness, and pH testing. Antibacterial activity was determined using the well diffusion method at extract concentrations of 5%, 10%, and 15%, and the results were analyzed descriptively. The findings indicated that the ethanolic extract contained flavonoids. Emulgels at all concentrations exhibited acceptable physical appearance and a pH suitable for topical use (pH 5–6). However, adhesiveness remained suboptimal (<4 s), and only the 15% formulation met the spreadability criterion, with a value of 5.56 cm. All emulgel concentrations demonstrated antibacterial activity against S. aureus, producing inhibition zones of 10 mm (5%), 12 mm (10%), and 14.6 mm (15%), whereas clindamycin cream (positive control) yielded a 40 mm inhibition zone.